1997
DOI: 10.1152/ajpendo.1997.273.6.e1203
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines increase monocyte TNF receptors and inhibit TNF through β2-adrenoreceptor activation

Abstract: Postinjury deficits in monocyte tumor necrosis factor receptors (moTNFR) activity may alter beneficial functions during an inflammatory response. Several counter-regulatory hormones elicited during inflammation may modulate tumor necrosis factor (TNF) activity, but little is known about their influence on moTNFR. Also, catecholamines inhibit TNF production, but the adrenoreceptor mechanism of this effect has not been fully clarified. To determine the effect of catecholamines and corticosteroids on moTNFR, whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 29 publications
1
46
0
2
Order By: Relevance
“…Catecholamines act through ␤-adrenergic receptors to regulate the expression of the cytokine receptors (8). Epinephrine and norepinephrine have immunosuppressive effects (13).…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamines act through ␤-adrenergic receptors to regulate the expression of the cytokine receptors (8). Epinephrine and norepinephrine have immunosuppressive effects (13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition pregnancy to be associated with changes of several hormones, including, estrogen, progesterone, cortisol and 1, 25 dihydroxyvitamin D3 (Henricks et al, 1972;Smith et al, 1973;Ardawi et al, 1997). Some of these hormones such as cortisol and catecholamines and 1, 25 dihydroxy D3 are potent inhibitor of TNF-α production by monocyte/macrophage (DeRijk et al, 1997;Guirao et al, 1997;Anand et al, 2009;Ito et al, 2002). In other study has been shown, plasma concentration of cortisol was elevated more during late pregnancy than early pregnancy (Kirwan et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, enhanced cytokine production was associated with hyperactivity of SNS (Petretta et al 2000) and high plasma norepinephrine levels (Kinugawa et al 2003). Furthermore, it has been shown in vivo and in vitro that cytokine production by the heart may be regulated by SNS through β-adrenergic receptors (Guirao et al 1997;Kan et al 1999;Prabhu et al 2000). Chronic β-adrenergic stimulation with isoproterenol enhances gene expression and protein production of TNF-α, IL-1 β, and IL-6 in the heart while β-adrenergic receptors antagonists inhibit these productions (Kan et al 1999).…”
Section: A B a Bmentioning
confidence: 99%